31P chemical shift tensors for canonical and non-canonical conformations of nucleic acids: a DFT study and NMR implications - Přecechtělová, Jana; Padrta, Petr; Munzarová, Markéta; Sklenář, Vladimír (The journal of physical chemistry. B, 2008)
31P chemical shift anisotropy (CSA) tensors have been calculated for a set of selected DNA and RNA backbone conformations using density functional theory. The set includes canonical A-RNA, A-DNA, BI-DNA, BII-DNA, ZI-DNA, and ZII-DNA as well as four A-RNA-type, seven non-A-RNA-type, and three non-canonical DNA conformations. Hexahydrated dimethyl phosphate has been employed as a model. The 31P chemical shift tensors obtained are discussed in terms of similarities in the behavior observed for gauche-gauche (gg) and gauche-trans (gt) conformations around the P-O bonds. We show that torsion angles alpha and zeta are major determinants of the isotropic chemical shift deltaiso and of the deltaCSA11 component of the traceless chemical shift tensor, which is revealed in separate ranges of both deltaiso and deltaCSA11 for gg- and gt-conformers, respectively. A clear distinction between the two conformation types has not been found for the deltaCSA22 and deltaCSA33 components, which is attributed to their different directional properties. The 31P CSA tensors exhibit considerable variations resulting in large spans of approximately 16 ppm for deltaCSA11 and approximately 22 ppm for deltaCSA22 and deltaCSA33. We examine the consequences of the CSA variations for predicting the chemical shift changes upon partial alignment deltacsa and for the values of CSA order parameters extracted from the analysis of 31P NMR relaxation data. The theoretical 31P CSA tensors as well as the experimental 31P CSA tensor of barium diethyl phosphate (BDEP) are used to calculate deltacsa for two eclipsed orientations of the CSA and molecular alignment tensors. Percentage differences between the CSA order parameters obtained using the theoretical 31P CSA tensors and the experimental 31P CSA tensor of BDEP, respectively, are also determined.
Keywords: financování organizované; počítačová simulace; Organophosphorus Compounds; Quantum Theory; fosfor; Anisotropy; izotopy fosforu; nukleové kyseliny; Nucleic Acid Conformation; organofosforové sloučeniny; Nucleic Acids; Computer Simulation; konformace nukleové kyseliny; Financing, Organized; magnetická rezonanční spektroskopie; Phosphorus; Oxygen; anizotropie; Phosphorus Isotopes; Magnetic Resonance Spectroscopy; kvantová teorie; kyslík